Efficacy of inactivated trivalent influenza vaccine in rural India: a 3-year cluster-randomised controlled trial. Issue 7 (July 2019) - Sullender, Wayne M; Fowler, Karen B; Gupta, Vivek; Krishnan, Anand; Ram Purakayastha, Debjani; Srungaram VLN, Raghuram; Lafond, Kathryn E; Saha, Siddhartha; Palomeque, Francisco S; Gargiullo, Paul; Jain, Seema; Lal, Renu; et al.
Summary: Background: Paediatric vaccination against influenza can result in indirect protection, by reducing transmission to their unvaccinated contacts. We investigated whether influenza vaccination of children would protect them and their household members in a resource-limited setting. Methods: We did a cluster-randomised, blinded, controlled study in three villages in India. Clusters were defined as households (ie, dwellings that shared a courtyard), and children aged 6 months to 10 years were eligible for vaccination as and when they became age-eligible throughout the study. Households were randomly assigned (1:1) by a computer-based system to intramuscular trivalent inactivated influenza vaccine (IIV3) or a control of inactivated poliovirus vaccine (IPV) in the beginning of the study; vaccination occurred once a year for 3 years. The primary efficacy outcome was laboratory-confirmed influenza in a vaccinated child with febrile acute respiratory illness, analysed in the modified intention-to-treat population (ie, children who received at least one dose of vaccine, were under surveillance, and had not an influenza infection within 15 days of last vaccine dose). The secondary outcome for indirect effectiveness (surveillance study) was febrile acute respiratory illness in an unvaccinated household member of a vaccine study participant. Data from each year (year 1: November, 2009, to October, 2010; year 2: October, 2010, to October, 2011; and year 3: October, 2011, to May, 2012) were analysed separately. Safety was analysed among all participants who were vaccinated with at least one dose of the vaccine. This trial is registered with ClinicalTrials.gov, number NCT00934245 . Findings: Between Nov 1, 2009, to May 1, 2012, we enrolled 3208 households, of which 1959 had vaccine-eligible children. 1010 households were assigned to IIV3 and 949 households were assigned to IPV. In 3 years, we vaccinated 4345 children (2132 with IIV3 and 2213 with IPV) from 1868 households (968 with IIV3 and 900 with IPV) with 10 813 unvaccinated household contacts. In year 1, influenza virus was detected in 151 (10%) of 1572 IIV3 recipients and 206 (13%) of 1633 of IPV recipients (total IIV3 vaccine efficacy 25·6% [95% CI 6·8–40·6]; p=0·010). In year 2, 105 (6%) of 1705 IIV3 recipients and 182 (10%) of 1814 IPV recipients had influenza (vaccine efficacy 41·0% [24·1–54·1]; p<0·0001). In year 3, 20 (1%) of 1670 IIV3 recipients and 81 (5%) of 1786 IPV recipients had influenza (vaccine efficacy 74·2% [57·8–84·3]; p<0·0001). In year 1, total vaccine efficacy against influenza A(H1N1)pdm09 was 14·5% (–20·4 to 39·3). In year 2, total vaccine efficacy against influenza A(H3N2) was 64·5% (48·5–75·5). Total vaccine efficacy against influenza B was 32·5% (11·3–48·6) in year 1, 4·9% (–38·9 to 34·9) in year 2, and 76·5% (59·4–86·4) in year 3. Indirect vaccine effectiveness was statistically significant only in year 3 (38·1% [7·4–58·6], p=0·0197) when influenza was detected in 39 (1%) of 4323 IIV3-allocated and 60 (1%) of 4121 IPV-allocated household unvaccinated individuals. In the IIV3 group, 225 (12%) of 1632 children in year 1, 375 (22%) of 1718 in year 2, and 209 (12%) of 1673 in year 3 had an adverse reaction (compared with 216 [13%] of 1730, 380 [21%] of 1825, and 235 [13%] of 1796, respectively, in the IPV group). The most common reactions in both groups were fever and tenderness at site. No vaccine-related deaths occurred in either group. Interpretation: IIV3 provided variable direct and indirect protection against influenza infection. Indirect protection was significant during the year of highest direct protection and should be considered when quantifying the effect of vaccination programmes. Funding: US Centers for Disease Control and Prevention.